ESTUDO DA REAÇÃO DE REDUÇÃO DE OXIGÊNIO SOBRE ELETRODOS À BASE DE TETRAMETÓXIFENILPORFIRINAS PARA APLICAÇÕES EM CÉLULAS A COMBUSTÍVEL DE BOROIDRETO DIRETO - Botelho, Alielson Corrêa (2012)
The oxygen reduction reaction (ORR) in 1.0 mol/L KOH solutions catalyzed by FeTMPP/C and CoTMPP/C was investigated in absence and presence of BH4- anions with concentrations varying from 10-7 to 1.0 mol/L. Similar cyclic voltammetry and rotating disk electrode experiments have been also performed the commercial E-TEK Pt/C electrocatalysts. In absence of BH4- anions, the ORR proceeds via a direct 4 electron pathway on FeTMPP/C and Pt/C and via a peroxide pathway involving (2-electron process) on CoTMPP/C and Au/C catalysts. In addition, Pt/C presented the most positive onset potential for the reaction. In presence of BH4- anions, a drastic loss in the catalytic activity of the Pt/C electrode was observed, even for concentrations as low as 10-7 mol/L. The effect of temperature on the ORR was studied and from 20ºC up to 60ºC the diffusion limited current densities remained nearly constants. At 80ºC, a decrease in the current of density was observed, probably due to a decrease in the oxygen concentration and viscosity of the solution. Arrhenius plots [ln (k) vs. T-1] were used to evaluate the activation s energy (Ea) of the ORR in absence of borohydride and resulted in 47.6 kJ/mol and 50.3 kJ/mol for Pt/C and FeTMPP/C, respectively. In presence of borohydride in solution, the Ea value for Pt/C showed a pronounced decrease to 38.7 kJ/mol, due to borohydride oxidation as a parallel reaction, while for FeTMPP/C the value calculate was 52.7 kJ/mol, i.e., remained practically constant. Such results indicates that FeTMPP is an efficient catalyst for ORR in alkaline solutions and tolerant to BH4 anions.